L’économie tunisienne face à la crise de la dette des subprimes et la crise des dettes souveraines européenne - Zied Akrout; Adel Khadimallah (L’Année du Maghreb)
The subprime mortgage crisis seriously confounded world financial markets, pushing the real economies of Tunisia’s trading partners into recession. In addition, deterioration of public finance and the downgrading of sovereign national debt further impacted members of the euro zone, undermining the credibility of the single European currency. The combination of factors greatly impacted Tunisian economic performance, leading to a negative current account trade balance as of July 2012. The Tunisian current account balance as of July 2012 was -6,366.4 million dinars (MD) a decrease of 2,230.2 MD and 1,478.3 MD respectively over 2011 (when the current account balance was -4,136.2MD) and 2010 (when the current account balance was -4,888.1MD).